DOMAIN INDEPENDENT SERVER FOR DOCUMENT MANAGEMENT SYSTEM - M. V. Sterjanov; I. V. Baidakov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Domain independent server for document management system is detailed. Server plays a role of basic software which allows to extend functionality of the system. Main objective of suggested server is processing requests from representation layer. Server’s architecture and functionality are also reviewed.